Checklist of oribatid mites (Acari, Oribatida) of the Transcarpathian lowland, Ukraine - Habriel H. Hushtan; Kateryna V. Hushtan; Sergii V. Glotov (Persian Journal of Acarology)
This article summarizes knowledge on the species composition of oribatid mites of the Transcarpathian lowlands. In total, 174 species of oribatid mites (97 genera and 50 families) are recorded from 53 localities and 18 types of biotopes. Ecological and distributional data for each species are specified. The fauna is compared with that of the other areas of the Pannonian lowlands (Hungary, Slovakia, and Romania). Two species, Rhinoppia similifallax Subías & Mínguez, 1986 and Galumna bimorpha Mahunka, 1987 are first records from Ukraine. Two other species, Cosmochthonius tenuisetus Gordeeva, 1980 and Ceratozetella maxima (Berlese, 1908) are found for the first time from the Pannonian Plain.